Assessment Principles and Practices Quality Assessments in A Digital Age - Isnaini Isnaini; Sunimaryanti Sunimaryanti; Lesis Andre (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research aims to know the application of assessment principles and the quality of assessment in the digital age. The method of writing in this study uses the literature method by applying the principle of quality and quality of its implementation in the digital age through a similar research theme. The results of this study have advantages and disadvantages to the principle of assessment and quality of assessment in the digital age. The benefits are direct feedback, improving autonomy, institution, and self-regulation of learners, collaborative learning, authenticity, broader measurement, fast and flexible response, improving efficiency and reducing teacher performance, integrating formative assessment, and validity and reliability of assessment, while the shortcomings inconsistent, infrastructure barriers, and fraud. There are five principles of assessment of the digital age, namely authentic assessment, accessible and inclusive assessment, appropriately automated assessment, continuous assessment, and security assessment. Although there are advantages and disadvantages of the assessment principle and quality non-formal education of digital age assessment, but there are five recommendations of digital assessment applications: Nearpod, Spelling Test, GoClass App, Guru Clicker, etc. ClassTalk applications.Keyword: Assessment Principles, Practices Quality Assessments, Digital Age